2009
DOI: 10.1126/science.1170160
|View full text |Cite
|
Sign up to set email alerts
|

Coding-Sequence Determinants of Gene Expression in Escherichia coli

Abstract: Synonymous mutations do not alter the encoded protein, but they can influence gene expression. To investigate the mechanisms, we engineered a synthetic library of 154 genes that vary randomly at synonymous sites, but all encode the same green fluorescent protein. When expressed in E. coli, GFP protein levels varied 250-fold across the library. GFP mRNA levels, mRNA degradation patterns, and bacterial growth rates also varied, but codon bias did not correlate with gene expression. Rather, the stability of mRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

100
1,658
25
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,340 publications
(1,849 citation statements)
references
References 35 publications
100
1,658
25
4
Order By: Relevance
“…Pervasive variation in the frequencies of synonymous codons across genes and genomes (codon usage bias) 1 suggests that selection may favour some synonymous codons over others. Moreover, direct measures of the impact of synonymous mutations from nucleotide replacement studies demonstrate that they can impact gene expression 2,3 , presumably through changes to the rate or accuracy of transcription and/or translation 4 , mRNA stability and folding 5 , protein secondary structure 6,7 and even fitness 3,[8][9][10][11] . Taken together, these results suggest that the frequency of at least some synonymous mutations is governed by selection.…”
mentioning
confidence: 99%
“…Pervasive variation in the frequencies of synonymous codons across genes and genomes (codon usage bias) 1 suggests that selection may favour some synonymous codons over others. Moreover, direct measures of the impact of synonymous mutations from nucleotide replacement studies demonstrate that they can impact gene expression 2,3 , presumably through changes to the rate or accuracy of transcription and/or translation 4 , mRNA stability and folding 5 , protein secondary structure 6,7 and even fitness 3,[8][9][10][11] . Taken together, these results suggest that the frequency of at least some synonymous mutations is governed by selection.…”
mentioning
confidence: 99%
“…However, at least some understanding of the dynamical regime in real organisms is now forthcoming. The assumption that translation initiation is the main limiting factor (Aitken, 2012) seems to be corroborated by Kudla et al (2009) who found that for E. coli the ribosome affinity to be the main determinant of gene expression, whereas local codon substitutions have a small effect only. This is interesting because an affinity limited regime would be inefficient in that it would leave ribosomes, which are expensive to make, unused.…”
Section: Discussionmentioning
confidence: 60%
“…Using Escherichia coli as a host Kudla et al (2009) measured the translation rates of an extensive library of synonymous sequences with widely varying speeds. The authors reported no correlation between codon adaptedness and translation rate.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, it is interesting to note that, among the several different ways by which translation can be regulated, the secondary structure of the 59 UTR is known to have a profound influence on translation efficiency [28]. Indeed, it has been previously shown that loose structures at the 59 end promotes whereas tight structures inhibits translation [29,30]. In support of such a model for translation of the Gata4 transcripts, E1a and E1b mRNAs precisely differ only by the extremity of their 59 UTR and this appears to be enough for generating mRNA variants with different predicted secondary structures [13].…”
Section: Discussionmentioning
confidence: 99%